Consumer response to food safety risk information - Hoffmann, Vivian; Murphy, Mike; Kariuki, Sarah (International Food Policy Research Institute, 2024)
Unsafe food imposes significant health and productivity burdens on developing countries. We test the impact of a simple information intervention through which low-income urban consumers in Kenya were provided information about the likelihood that maize flour from the formal and informal sector violated a food safety standard. We find a 42 percent increase in the share of households consuming the similarly priced, lower risk formal sector flour type at follow-up in the treatment group relative to the control group, from a base of 33 percent. The intervention was equally effective for households earning below and above the sample median income level. Our results demonstrate the potential for low-cost interventions to increase the salience of food safety as a product attribute in informal markets or where regulatory enforcement is weak.